A Comparative Study of Deixis Used by Foreign and Local English Teachers in Vocational High School - Mayori, Winda; Adi Jaya Putra, Nyoman; Suarnajaya, I Wayan (Journal of Education Reseach and Evaluation, 2020)
This study aims to analyze the types of deixis by using Levinson’s theory, find out the dominant types of deixis, and the reasons behind the uses of deixis by foreign and local English teachers. The study used a qualitative method particularly a case study. The data sources of this study were the foreign and local English teachers’ utterances. The data were obtained through a classroom observation and interview technique. The data were analysed using Miles and Hubermans’s interactive model. The findings showed that five types of deixis were found in the foreign and local English teacher’s utterances, namely person deixis, place deixis, time deixis, discourse deixis, and social deixis. The dominant types of deixis in both the English teachers’ utterances were person deixis.  The reasons behind the uses of deixis were also explained in this study